Digital Transformation and Corruption Control: Unveiling the Paradox of Cybersecurity in Global Governance - Chang, Nicholas (Accounting Study Program, Universitas Ciputra Surabaya, 2026)
This study examines the association between digital transformation, represented by blockchain, e-government, and cybersecurity, and corruption, proxied by the Corruption Perceptions Index (CPI), within the framework of good governance and Sustainable Development Goal 16. Using a quantitative approach, this study analyzes secondary data from 23 countries characterized by relatively high levels of blockchain adoption. Multiple linear regression analysis was employed using SPSS version 27. The results indicate that blockchain and e-government are positively and significantly associated with CPI, suggesting that higher levels of digital readiness tend to coincide with lower perceived corruption within the sample. E-government shows the strongest association within the model, which is consistent with its potential relevance to transparency, accountability, and public service efficiency. In contrast, cybersecurity is negatively and significantly associated with CPI, indicating that stronger cybersecurity capacity does not necessarily correspond to lower perceived corruption and may reflect tensions between control and transparency when not supported by appropriate governance frameworks. These findings suggest that digital transformation alone is insufficient to combat corruption. Its effectiveness depends on alignment with good governance principles, particularly transparency and accountability. This study contributes by providing an integrated perspective on digital transformation and offers implications for policymakers in designing balanced digital governance strategies.